PERSPEKTIF BIOPSIKOSPIRITUAL PADA PASIEN PRURITUS SINE MATERIA - SANTOSA, I KETUT ARYA; ARIANI, NI KETUT PUTRI; SETIONO, DENNIS PRISCILLA; TRISNOWATI, RINI; MAHARDIKA, I KOMANG ANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Pruritus Sine Materia is generalized pruritus without primary skin lession. It’s also catagorized as functional itch disorder or psychogenic pruritus. It is important to know the biopsychosociospiritual perspective as a psychiatrist in order to provide holistic therapy. Female, 40 years old, married, Moslem, lives in a boarding house, was consulted by a dermatovenerologist with Pruritus Sine Materia, complaints of itching without primary lesions since 3 months of marriage. She felt itchy in the local body area that is in contact with husband and his stuff. Skin test results are normal, without allergies. When she got married, she was surprised knowing that the husband's dog slept in the boarding room and on the mattress several times. There was saliva and dog urine on things in the room. The patient reminded his husband several times that they were Moslem, she hoped her husband would be aware of his behavior that was not according to religion. The patient is diagnosed with other somatoform disorder. She was prescribed antidepressant and benzodiazepine as pharmacological approach and got education, support, also behaviour therapies for her psychological capability to control the itch-scratch process. According to Islamic law, dogs are classified as extreme najis (mughallazhah), when they are exposed to sweat, saliva, feces and urine. Najis means ritually unclean, contact with it puts a Moslem in a state of impurity or disgust. The patient is faced with feelings of guilt because she does not carry out Islamic law properly. This causes negative religious coping related to the occurrence of anxiety and depression, which is a risk factor for psychogenic pruritus, Pruritus Sine Materia. It is important to understand the biopsychosociospiritual perspective to be able to determine the appropriate and holistic pharmacological and non-pharmacological treatment. ABSTRAKPruritus Sine Materia adalah pruritus generalisata tanpa lesi kulit primer. Ini juga dikategorikan sebagai gangguan gatal fungsional atau pruritus psikogenik. Pentingnya mengetahui pandangan biopsikosociospiritual sebagai seorang psikiater agar dapat memberikan terapi holistik. Sebuah studi kasus pada pasien wanita, 40 tahun, menikah, beragama Islam, tinggal di kos, berkonsultasi ke dokter kulit dengan Pruritus Sine Materia, keluhan gatal-gatal tanpa lesi primer sejak 3 bulan menikah. Dia merasa gatal di area tubuh yang bersentuhan dengan suami dan barang-barangnya. Hasil tes kulit normal, tanpa alergi. Saat menikah, ia terkejut mengetahui anjing milik suaminya beberapa kali tidur di kamar kos dan di kasur. Ada air liur dan urin anjing pada benda-benda di dalam ruangan. Pasien beberapa kali mengingatkan suaminya bahwa dirinya beragama Islam, ia berharap suaminya sadar akan perilakunya yang tidak sesuai agama. Pasien didiagnosis dengan gangguan somatoform lainnya. Dia diberi resep antidepresan dan benzodiazepin sebagai pendekatan farmakologis dan mendapatkan pendidikan, dukungan, serta terapi perilaku atas kemampuan psikologisnya dalam mengendalikan proses gatal-garuk. Menurut hukum Islam, anjing tergolong najis ekstrem (mughallazhah), jika terkena keringat, air liur, feses, dan urine. Najis berarti najis secara ritual, kontak dengan najis membuat seorang Muslim berada dalam keadaan najis atau jijik. Pasien dihadapkan pada perasaan bersalah karena tidak menjalankan syariat Islam dengan baik. Hal ini menyebabkan koping keagamaan yang negatif berhubungan dengan terjadinya kecemasan dan depresi yang merupakan faktor risiko terjadinya pruritus psikogenik, Pruritus Sine Materia. Penting untuk memahami perspektif biopsikosociospiritual untuk dapat menentukan pengobatan farmakologis dan nonfarmakologis yang tepat dan holistik.